Gene Identification and Characterization of Correlations for DEPs_DEGs Same Trend Responding to Salinity Adaptation in Scylla paramamosain - Huan Wang; Hongling Wei; Lei Tang; Junkai Lu; Changkao Mu; Chunlin Wang (International Journal of Genomics)
Scylla paramamosain is a commercially important species distributed along the coast of southern China and other Indo-Pacific countries. Sudden salinity drop exceeding the adjustment capability of S. paramamosain can result in damage or even mortality. In our previous study, we had analyzed the mechanism of adapting sudden drop in salinity from the level of transcriptomics and proteomics, respectively. This study performed a correlation analysis of RNA sequencing transcriptomics and iTRAQ proteomics in order to investigate the adaptation mechanisms to sudden salinity drop from 23‰ to 3‰. There were 3954 correlations and a total of 15 correlations for differentially expressed proteins (DEPs) and differentially expressed genes (DEGs) from proteomics and transcriptomics. The correlation between DEPs and DEGs was 0, and the Spearman correlation coefficient of the same trend correlation for DEPs and DEGs was the highest, reaching 0.9080. KEGG pathway enrichment correlation revealed that protein digestion and absorption (Ko04974), proximal tubule bicarbonate (Ko04964), and bile secretion (Ko04976) played important roles in Na+/H+ and Na+/K+ exchange. In addition, important genes related to osmoregulation, such as ion transport and carbonic anhydrase, were also detected in the correlation analysis for same trend DEPs_DEGs. In conclusion, the proteome and transcriptome correlation results from this study indicate that ion transport plays a critical role in the adaptation of S. paramamosain to sudden reduction in salinity.